A 1‐year, prospective, observational study of Japanese outpatients with type 1 and type 2 diabetes switching from insulin glargine or detemir to insulin degludec in basal–bolus insulin therapy (Kumamoto Insulin Degludec Observational study). Issue 5 (19th March 2016) - Shimoda, Seiya; Sato, Miki; Sekigami, Taiji; Motoshima, Hiroyuki; Yoshimura, Ryohei; Fukuda, Kazuki; Matsuo, Yasuto; Noda, Hideyuki; Okubo, Mina; Ichimori, Shinji; Fujisawa, Kazuo; Fukunaga, Makiko; et al.
Abstract: Aims/Introduction: The aim of the present prospective observational study was to assess long‐term efficacy and safety of insulin degludec as a part of a basal–bolus therapy for Japanese patients with type 1 or type 2 diabetes in routine clinical practice. Materials and Methods: In the present study, 93 type 1 diabetes patients and 135 type 2 diabetes patients treated with insulin glargine or detemir were switched from their basal insulin to insulin degludec. The primary end‐points were the changes in glycated hemoglobin (HbA1c) from baseline at 3, 6 and 12 months. The secondary end‐points were changes in body mass index, insulin dose, frequency of hypoglycemia and adverse events. Results: HbA1c levels from baseline were significantly reduced at 3, 6, and 12 months by 0.4, 0.4 and 0.3% in type 1 diabetes patients, respectively, and by 0.5, 0.5 and 0.3% in type 2 diabetes patients, respectively. Body mass index in type 1 diabetes patients increased significantly ( P < 0.05), whereas that in type 2 diabetes patients did not change. Basal insulin dose decreased significantly at 3 months after switching ( P < 0.05), and returned baseline dose at 12 months in type 1 diabetes and type 2 diabetes patients. The frequency of both total and nocturnal hypoglycemia decreased significantly in type 1 diabetes and type 2 diabetes patients ( P < 0.05). The result of multiple regression analysis showed that baseline HbA1c was a significant independent variable of the percentage change in HbA1c with switching. Conclusion: In both type 1 diabetes and type 2 diabetes patients, switching from insulin glargine or insulin detemir to insulin degludec led to improvement of glycemic control with a significant reduction of hypoglycemia. Abstract : In both T1D and T2D subjects treated with BBT, switching from insulin glargine or detemir to insulin degludec led to improvement of glycemic control with a significant reduction of hypoglycemia.